Recent Developments in the Immobilization of Laccase on Carbonaceous Supports for Environmental Applications - A Critical Review - Adamian, Younes; Lonappan, Linson; Alokpa, Komla; Agathos, Spiros N.; Cabana, Hubert (Frontiers in Bioengineering and Biotechnology, 2021)
Τhe ligninolytic enzyme laccase has already proved its potential for environmental applications. However, the industrial application of free laccase is limited due to low stability, poor reusability, and high costs. Immobilization has been considered as a powerful technique to enhance laccase’s industrial potential. In this technology, appropriate support selection for laccase immobilization is a crucial step since the support could broadly affect the properties of the resulting catalyst system. Through the last decades, a large variety of inorganic, organic, and composite materials have been used in laccase immobilization. Among them, carbon-based materials have been explored as a support candidate for immobilization, due to their properties such as high porosity, high surface area, the existence of functional groups, and their highly aromatic structure. Carbon-based materials have also been used in culture media as supports, sources of nutrients, and inducers, for laccase production. This study aims to review the recent trends in laccase production, immobilization techniques, and essential support properties for enzyme immobilization. More specifically, this review analyzes and presents the significant benefits of carbon-based materials for their key role in laccase production and immobilization.